2023
DOI: 10.3390/ijms24021381
|View full text |Cite
|
Sign up to set email alerts
|

AaCaMKs Positively Regulate Development, Infection Structure Differentiation and Pathogenicity in Alternaria alternata, Causal Agent of Pear Black Spot

Abstract: Calcium/calmodulin-dependent protein kinase (CaMK), a key downstream target protein in the Ca2+ signaling pathway of eukaryotes, plays an important regulatory role in the growth, development and pathogenicity of plant fungi. Three AaCaMKs (AaCaMK1, AaCaMK2 and AaCaMK3) with conserved PKC_like superfamily domains, ATP binding sites and ACT sites have been cloned from Alternaria alternata, However, their regulatory mechanism in A. alternata remains unclear. In this study, the function of the AaCaMKs in the devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Total RNA was extracted from tea plant leaves using the FastPure Plant Total RNA Isolation Kit (Polysaccharides and Polyphenolics‐rich) (Nanjing Vazyme Biotech Co., Ltd., China), and single‐strand cDNA was synthesized by the HiScript II 1st Strand cDNA Synthesis Kit (+gDNA wiper) (Nanjing Vazyme Biotech Co.). qRT–PCR analysis was performed as previously described (Jiang, Cao, et al., 2023; Jiang, Li, et al., 2023). The data were normalized to the expression of CsPTB (Cao et al., 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was extracted from tea plant leaves using the FastPure Plant Total RNA Isolation Kit (Polysaccharides and Polyphenolics‐rich) (Nanjing Vazyme Biotech Co., Ltd., China), and single‐strand cDNA was synthesized by the HiScript II 1st Strand cDNA Synthesis Kit (+gDNA wiper) (Nanjing Vazyme Biotech Co.). qRT–PCR analysis was performed as previously described (Jiang, Cao, et al., 2023; Jiang, Li, et al., 2023). The data were normalized to the expression of CsPTB (Cao et al., 2022).…”
Section: Methodsmentioning
confidence: 99%
“…For example, Mps1p , a PKc gene in M. oryzae , is a stealth factor that conceals the cell wall of infectious hyphae and prevents recognition by hosts [ 80 ]. Previous studies have shown that three AaCaMKs genes encoding PKc_like kinases in A. alternata regulate infection structure differentiation and pathogenicity [ 81 ]. The APH_ChoK_Like family employs ATP-mediated phosphate transfer to chemically modify and inactivate aminoglycoside antibiotics such as streptomycin and kanamycin [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research has also found that both melanin synthesis and infection of cotton by V. dahliae are coupled through transmembrane protein VdSho1 , and the MAPK signal module Ste50-Ste11-Ste7 is involved in this coupling process ( Li et al, 2019 ). In A. alternata , sho-MAPK, cAMP, and Ca 2+ signaling pathways are involved in infection structure formation induced by physicochemical cues from pear fruit peel wax, affecting the synthesis of melanin at the same time ( Liu et al, 2021 ; Zhang et al, 2021 ; Jiang et al, 2023 ). The above reports suggest that melanin may be directly or indirectly involved in infection structure formation or infection process in plant pathogenic fungi, which only form colorless appressorium.…”
Section: Discussionmentioning
confidence: 99%